Meaning in military service among reservists: Measuring the effect of prosocial motivation in a moderated-mediation model - Smaliukienė, Rasa; Bekesiene, Svajone; Kanapeckaitė, Rosita; Navickienė, Olga; Meidutė-Kavaliauskienė, Ieva; Vaičaitienė, Ramutė (Frontiers in Psychology, 2023)
Background: The meaningful commitment to serve one’s country and the desire to benefit others make military service unique compared to other human activities. This is especially true for the army reservists who are typically working in the civilian labor market and taking part in the short-term military training or military missions. Recent studies have reported that both of these phenomena – that is, prosocial motivation and meaning in military service, have a major impact on military effectiveness, which in turn has attracted attention among scholars and practitioners. Still, today’s scholarly publications provide limited insights into the effects and influences of prosocial motivation on the meaning in military service. To fill this gap in research, this study contributes to our understanding of direct, mediated and moderated processes that link prosocial motivation to the meaning in military service among reservists. Specifically, the objective of this study was to examine both direct and indirect pathways linking prosocial motivation and meaning in military service. The former analyzed a direct effect, whilst the latter included the effects of the role fit within the military environment, soldiers’ self-efficacy, and socio-moral climate of military organization, i.e. variable that make military service exceptional activity. Results: Prosocial motivation assumes meaning in military service among reservists through different, yet related, pathways. The direct pathway confirmed that reserve soldiers with higher levels of prosocial motivation experience a higher level of meaning in service. The indirect pathway indicated that the role fit mediated this relationship. Following indirect pathway, we found that prosocial motivation was a significant predictor of role fit, and role fit was a significant predictor of meaning in military service. Finally, we confirmed the moderated mediation effects of self-efficacy and socio-moral climate in our suggested models.